2013
DOI: 10.1007/s10096-013-1966-x
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between Clostridium-difficile infection and human gut concentrations of Bacteroidetes phylum and clostridial species

Abstract: We aimed to assess differences in bacterial intensities of Bacteroidetes phylum and different clostridial species in the human intestines with respect to C. difficile infection. Patients with a stool assay for C. difficile toxin were identified via the microbiology laboratory in our institute. Bacterial populations were quantified from stool samples of four groups of patients: Group I-patients with C. difficile associated diarrhea (CDAD); Group II-asymptomatic C. difficile carriers; Group III-patients with non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 19 publications
4
25
0
Order By: Relevance
“…Although the differences were insignificant, a previous study showed that phylum distribution in IBD patients harbored significantly fewer Bacteroidetes than that in healthy subjects [70]. Furthermore, an inverse association has been reported between infection with C. difficile and abundance of Bacteroidetes [71]. In addition, we observed that the abundance ratio of the Firmicutes/Bacteroidetes phyla was higher in the DSS + CD group than in the normal group, supporting the findings of a previous study [72].…”
Section: Discussionsupporting
confidence: 90%
“…Although the differences were insignificant, a previous study showed that phylum distribution in IBD patients harbored significantly fewer Bacteroidetes than that in healthy subjects [70]. Furthermore, an inverse association has been reported between infection with C. difficile and abundance of Bacteroidetes [71]. In addition, we observed that the abundance ratio of the Firmicutes/Bacteroidetes phyla was higher in the DSS + CD group than in the normal group, supporting the findings of a previous study [72].…”
Section: Discussionsupporting
confidence: 90%
“…[1][2][3] Clostridium difficile infection (CDI) is thought to result from a diminished indigenous colonic flora, particularly after the use of broad spectrum antibiotics, that allows C. difficile to proliferate into the resultant ecological void. [4][5][6] Recurrent Clostridium difficile infection (rCDI) is an increasing problem and hypervirulent strains have emerged 7-9 resulting in increased morbidity and mortality. 10 Faecal microbiota transplant (FMT) has become the standard of care for patients with rCDI as a result of randomised control trial evidence of its superiority to traditional antibiotic therapy alone.…”
Section: Resultsmentioning
confidence: 99%
“…Persons who develop CDI are known to have a decrease in the alpha diversity of the faecal microbiome compared to healthy controls, and are more likely to have a relative increase in the abundance of certain Firmicutes, specifically Enterococcus , Lactobacillus species, as well as a reduction in Bacteroidetes, as well as a decrease in Clostridiales Incertae Sedis XI, a non‐toxigenic clostridium which may competitively inhibit the proliferation of C. difficile . Clindamycin and beta‐lactams, the antibiotics most strongly associated with the development of CDI, also causes severe depletion in colonic Bacteroidetes, and an increase in Gram positive cocci, mostly Firmicutes .…”
Section: Discussionmentioning
confidence: 99%